Logvinenko Y. Postmodernism as the subject of study in Ukrainian literature - Logvinenko Y. (Philological Treatises, 2020)
The article attempts to trace the adaptation of postmodern worldview and understanding the discourse of two directions in the art of the late twentieth century which is based on the Ukrainian art: modernism and postmodernism. Attention is also taken to the political situation in the society, particularly post-totalitarian, which affected the understanding and perception of postmodern by artists and critics.